Building Students’ Character Based on Maqāṣid al-Sharī'ah: Perspectives of Parents, Teachers, and Community Members in Banda Aceh - Mahmud, Salami; Sri Rahmi, Sri Rahmi; Nufiar, Nufiar; Nurbayani, Nurbayani; Nurdin, Realita (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
To build students' character, the Indonesian government has made various efforts, one of which is updating the curriculum to make it in line with the demands of the current times. Given the importance of character building since the school age, the Curriculum 2013 (K-13) was developed and it contains 18 national characters that must be promoted and developed during the learning process. However, until now the curriculum seems to have not been able to shape the character of students as expected. Therefore, this study aims to present alternative approaches in building student character. The approach is to form character at home, some are formed in school, and some are formed in society. This study provides concrete examples of character development contained in K-13 with an Islamic approach. This study is a qualitative study analyzed using Islamic education theory and maqāṣid al-sharī'ah. Data is collected in two ways, namely; in-depth interviews with informants and literature studies related to the discussion. The results show that religious characters such as honesty, discipline, independence, and responsibility are easier to build at home using the Islamic approach. Furthermore, the characters of tolerance, hard work, creativity, democracy, curiosity, nationalism, patriotism, respect for achievement, and fondness for reading are easier to develop at schools with an Islamic approach as well. Finally, it is easier to develop characters such as friendly/communicative, peace-loving, environmental awareness, and social characteristics within society. In addition, the 18 characters are related to the purpose of maqāṣid al-sharī'ah as well as Islamic education.